ISLAMIC FINANCING STRUCTURE AND BANK PROFITABILITY: THE MODERATING ROLE OF INFLATION IN INDONESIAN ISLAMIC BANKS - Fajar Ardiansyah (FEBI UIN Sunan Gunung Djati Bandung, 2026)
The increase in financing distribution in Islamic Commercial Banks in Indonesia is not always consistently followed by an increase in profitability. This phenomenon indicates a discrepancy with the financial intermediation theory. In addition, fluctuations in inflation as a macroeconomic factor may also influence this study examines the relationship between financing activities and the profitability of Islamic banks. Its main objective is to investigate the effects of Murabahah, Musyarakah, and Ijarah financing on the profitability of Islamic commercial banks, while also assessing the moderating role of inflation during the 2020–2024 period. The research employs a quantitative correlational design, utilizing monthly panel data obtained from the Financial Services Authority (OJK) and Bank Indonesia (BI). A saturated sampling approach is used, encompassing all Islamic commercial banks as the study sample. Data analysis is conducted through panel data regression using EViews software, with the moderating influence of inflation evaluated via Moderated Regression Analysis (MRA). The results indicate that Murabahah and Musyarakah financing have a significant effect on the profitability of Islamic commercial banks, whereas Ijarah financing does not demonstrate a significant impact. Furthermore, controlled inflation enhances the effect of Murabahah financing on profitability, while uncontrolled inflation diminishes the influence of Musyarakah financing and does not moderate the relationship between Ijarah financing and profitability. These findings highlight that the effectiveness of Islamic financing in improving and profitability. These results suggest that the effectiveness of Islamic financing in enhancing bank profitability is affected by the state of inflation, whether it is stable or unstable. Consequently, Islamic banks are encouraged to optimize their financing portfolio strategies and reinforce risk management practices in order to better respond to changing economic conditions.